Acquisition For Parents In The Acquisition Of Children's Language Skills At Citra Bakti Integrated Preschool - Ngura, Elisabeth Tantiana; Sayangan, Yohanes Vianey; Nou, Kresensiana (LPPM, STAI Al-Azhar Menganti, 2024)
his community service activity is carried out divided into two stages, namely the preparation stage and the implementation stage. The preparatory stage is carried out with the aim of making preparations such as preparing the necessary needs and asking for approval from the Principal of the Citra Bakti Integrated PAUD School by meeting in person and asking for permission verbally. At the implementation stage, the activities carried out are in the form of providing material about children's language development and parenting patterns through outreach to parents. The aim of the first two materials is to provide an understanding of the forms of language development in children, including how language acquisition is influenced by parental parenting. Language development in children occurs from the activities of hearing, seeing, and imitating the adults around them. Language is used to teach children about something. In the preparation stage, what is carried out is to see the parents' understanding of the language mastery process through socialization activities. The location of the activity is at the PAUD Terpadu Citra Bakti. The method used in this service is the lecture method, namely the method used by the team in providing material as resource persons to the accompanying participants, namely parents. Furthermore, the steps used in this community service go through two stage processes including: 1). Preparation phase; and 2). Implementation Stage. The result of this socialization activity is that the child's parents understand parenting patterns and the role of parental communication in the acquisition or development of language in children. Parents understand their role in communicating with children, because communication between parents and children can stimulate children's development, especially language development.